2013
DOI: 10.1242/dev.088559
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of a lymphomyeloid developmental switch controlled by PU.1, Notch and Gata3

Abstract: Hematopoiesis is a classic system with which to study developmental potentials and to investigate gene regulatory networks that control choices among alternate lineages. T-cell progenitors seeding the thymus retain several lineage potentials. The transcription factor PU.1 is involved in the decision to become a T cell or a myeloid cell, and the developmental outcome of expressing PU.1 is dependent on exposure to Notch signaling. PU.1-expressing T-cell progenitors without Notch signaling often adopt a myeloid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
134
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(140 citation statements)
references
References 40 publications
(51 reference statements)
4
134
0
Order By: Relevance
“…2E). For more extensive confirmation of the effects of this shRNA on Gata3 RNA and GATA-3 protein in the Adh.2C2 system, also see our recent report (43). Gata3 shRNA thus consistently lowered GATA-3 protein levels, despite its generally mild effect on RNA levels.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…2E). For more extensive confirmation of the effects of this shRNA on Gata3 RNA and GATA-3 protein in the Adh.2C2 system, also see our recent report (43). Gata3 shRNA thus consistently lowered GATA-3 protein levels, despite its generally mild effect on RNA levels.…”
Section: Resultsmentioning
confidence: 58%
“…PU.1 and GATA-3 act as antagonists in a network circuit in which GATA-3 restrains the ability of PU.1 to cause myeloid differentiation of DN pro-T cells, even when Spi1 expression itself is not under GATA-3 control (43). PU.1 naturally begins at high levels in ETP and DN2a cells, but falls immediately after GATA-3 reaches its peak (data not shown) (42), and our results suggested that GATA-3 might be required for this decline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies indicate that Pu.1 may be repressed gradually following T cell commitment from HSCs. In the thymus, antagonism between Notch and Pu.1 maintains the identity of T cell progenitor and prevents the adoption of myeloid fate (Del Real and Rothenberg, 2013;Franco et al, 2006). However, the underlying molecular mechanism for the downregulation of Pu.1 at the prethymic stage is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly and similar to the erythroid lineage, PU.1 expression is required in later T-cell progenitors to become repressed (Anderson et al, 2002), stays repressed in Th2 cells and CD8 T cells, but is reexpressed in Th9 cells (Gerlach et al, 2014). To achieve PU.1 repression in early T cells, the activity of PU.1 is antagonized by Notch, which is essential to push thymocytes into further maturation (Del Real and Rothenberg, 2013). Moreover, T-cell-specific repression of PU.1 expression is thought to be facilitated by binding of Runx1 to a silencer element located between the Sfpi1 promoter and its upstream enhancer elements (Zarnegar et al, 2010).…”
Section: Pu1 Cross-talk With Other Lineagespecific Transcription Facmentioning
confidence: 99%